A high-temperature and aging-resistant quantum dot diffusion plate and its preparation method
By using a combination of PC resin matrix and a variety of additives in the quantum dot diffusion plate, combined with CdSe/ZnS quantum dots, the heat resistance and aging problems of traditional diffusion plates are solved, and a high-performance quantum dot diffusion plate is realized. Excellent mechanical and optical properties.
Patent Information
- Application Number
- CN202410378172.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-03-29
AI Technical Summary
Due to the use of polystyrene (GPPS) substrates, existing quantum dot diffusion plates have problems such as poor heat resistance, easy softening and deformation, not aging resistance, easy yellowing, easy cracking and degradation of mechanical properties, and cannot meet the problems of high light transmission and low light transmission. Haze and uniform dispersion performance requirements.
A three-layer structure diffusion plate consisting of PC resin matrix, quantum dots and a variety of additives (antioxidants, UV absorbers, light stabilizers, mineral oils, brighteners, and foaming agents), through PC/SMA/organic The synergistic effect of silicon ternary blending system and foaming agent, combined with the introduction of CdSe/ZnS core-shell structure quantum dots, build a comprehensive anti-aging and optical performance improvement system.
It realizes excellent heat resistance, impact resistance, flame retardancy and high optical properties of the diffuser plate, significantly improves mechanical and optical properties, delays the aging process, and realizes high color gamut display, solving the traditional diffuser plate Multiple performance problems.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quantum dot diffusion plates, and in particular to a high temperature resistant and aging resistant quantum dot diffusion plate and a preparation method thereof. Background Art
[0002] Quantum dot diffusion plate is one of the key materials in quantum dot display technology, which can be used in fields such as liquid crystal backlight display and quantum dot electroluminescent display. At present, quantum dot diffusion plate usually uses polystyrene (GPPS) as the substrate, and extrudes the mixture of quantum dots and GPPS. However, the addition of quantum dots will lead to the decline of mechanical properties of GPPS substrate. In addition, GPPS in quantum dot diffusion plate also has problems such as low heat deformation temperature, poor heat resistance, easy softening and deformation, poor aging resistance, easy yellowing, easy cracking, and unstable color points. These defects seriously restrict the application and promotion of quantum dot diffusion plate.
[0003] The reasons for the above technical difficulties are as follows: (1) The glass transition temperature (Tg) of GPPS is relatively low, usually around 90-100°C, so the resulting quantum dot diffusion plate has poor heat resistance and is prone to softening and deformation during use; (2) The GPPS molecular structure contains unsaturated double bonds, which are easily degraded by light and oxygen, leading to aging, yellowing and cracking of the diffusion plate; (3) Introducing quantum dots into the GPPS substrate will destroy the interaction between the GPPS molecular chains, resulting in a decrease in mechanical properties; (4) A single GPPS substrate cannot meet the performance requirements of uniform dispersion of quantum dots, high light transmittance, and low haze. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a high temperature resistant and aging resistant quantum dot diffusion plate and a preparation method thereof. The diffusion plate has excellent heat resistance, impact resistance, flame retardancy and optical properties, and is light in weight, and can effectively solve many problems existing in GPPS-based quantum dot diffusion plates.
[0005] The contents of the present invention are as follows;
[0006] The object of the present invention is to provide a high temperature resistant and aging resistant quantum dot diffusion plate, the diffusion plate is composed of a PC resin matrix, quantum dots, and additives, including an upper layer, a middle layer, and a lower layer, wherein:
[0007] The intermediate layer material components include the following raw materials in parts by weight: 100 parts of polystyrene, 0.5-10 parts of quantum dots, 0.1-1 parts of antioxidants, 0.2-1 parts of ultraviolet absorbers, 0.2-1 parts of light stabilizers, 0.01-0.05 parts of mineral oil, and 0.01-0.05 parts of brighteners;
[0008] The upper layer and the lower layer material components include the following raw materials in parts by weight: 70-99.5 parts of PC resin, 1-10 parts of styrene-maleic anhydride copolymer, 1-10 parts of silicone resin, 0.1-1 parts of antioxidant, 0.2-1 parts of ultraviolet absorber, 0.2-1 parts of light stabilizer, 0.01-0.05 parts of mineral oil, 0.01-0.05 parts of brightener and 0.2-1 parts of foaming agent.
[0009] Specifically, the quantum dots are CdSe / ZnS core-shell structure quantum dots.
[0010] Specifically, the antioxidant is 2,2'-methylenebis(4,6-di-tert-butylphenol).
[0011] Specifically, the ultraviolet absorber is 2-hydroxy-4-hexyloxybenzophenone.
[0012] Specifically, the light stabilizer is decyl β-[3-(2H-benzotriazol-2-yl)-4-hydroxy-5-tert-butylphenyl]propionate.
[0013] Specifically, the mineral oil is polydimethylsiloxane.
[0014] Specifically, the brightening agent is benzophenone.
[0015] Specifically, the foaming agent is azodicarbonamide.
[0016] The above-mentioned method for preparing a high temperature resistant and aging resistant quantum dot diffusion plate comprises the following steps:
[0017] (1) Mixing the upper and lower surface materials: PC, styrene-maleic anhydride copolymer, silicone resin, antioxidant, ultraviolet absorber, light stabilizer, mineral oil, brightener and foaming agent are mixed in a high-speed mixer at a speed of 500-2000 rpm for 5-30 minutes according to the above proportions, and the mixing temperature is controlled at 20-80° C.;
[0018] (2) Mixing of the intermediate layer materials: GPPS, quantum dots, and antioxidant components are mixed in a stirring tank at a speed of 30-200 rpm for 10-60 min according to the above ratio, and the mixing temperature is controlled at 50-120° C.;
[0019] (3) Three-layer co-extrusion: the mixture prepared in step (1) and step (2) is respectively added to different feed ports of a co-extruder, and co-extruded at 185-230° C. and 10-40 MPa using a three-layer distribution die, with an extrusion output of 250-500 kg / h;
[0020] (4) Cooling and shaping: The co-extruded sheet is cooled by roller pressing, and the temperature gradually drops to room temperature to obtain the finished quantum dot diffusion plate.
[0021] Preferably, the temperature of each section of the single screw extruder in step (3) is set as follows: 185°C in zone 1, 195°C in zone 2, 215°C in zone 3, 215°C in zone 4, 230°C in zone 5, 220°C in zone 6, 215°C in zone 7, and 210°C at the die head; the extrusion rate is 320kg / h.
[0022] Compared with the prior art, the high temperature resistant and aging resistant quantum dot diffusion plate and its preparation method and its preparation method of the present invention can achieve the following beneficial effects:
[0023] 1. Synergistic toughening and strengthening effect of PC / SMA / organic silicone ternary blend system: PC is an amorphous polymer with excellent mechanical properties, heat resistance and optical properties, but slightly insufficient toughness. SMA contains maleic anhydride groups with strong polarity, which can be used as a compatibilizer to improve the compatibility of PC with other polymers. At the same time, SMA can also chemically modify PC by grafting or block copolymerization to form block copolymers such as PC-g-SMA or PC-b-SMA, thereby achieving the purpose of flexibility. Silicone resin contains Si-O-Si inorganic skeleton and organic groups such as phenyl, which have both the high strength and high modulus of inorganic materials and the flexibility of organic polymers. It can be used as a reinforcing toughening agent to significantly improve the mechanical properties of PC. In addition, the addition of silicone can also improve the fluidity and molding processing performance of the system. Therefore, the PC / SMA / organic silicone ternary system can play a synergistic effect of "1+1+1>3", which not only ensures the excellent mechanical properties of the quantum dot diffusion plate, but also takes into account the convenience of molding processing.
[0024] 2. Compounding of multiple additives to build a comprehensive aging protection system: During processing and use, polymers are prone to various aging behaviors such as thermal degradation, oxidative degradation, and light (ultraviolet) degradation, resulting in performance degradation. The present invention starts from multiple aspects and compounds a variety of high-efficiency additives for different aging pathways and mechanisms, thereby building a comprehensive three-dimensional anti-aging system. Among them, tert-butylphenol antioxidants can capture free radicals generated during the oxidation process of polymers and block the auto-oxidation cycle; ultraviolet absorbers can absorb and convert ultraviolet light energy to prevent polymers from absorbing ultraviolet light and causing degradation; light stabilizers such as HALS can remove free radicals and peroxides during the oxidation process. These three types of additives can play a synergistic role to curb the occurrence of various photo-oxidation aging behaviors from the source. At the same time, silicone resin can also be used as an optical isolation layer to block the transmission of ultraviolet light. Therefore, the anti-aging protection system composed of the above-mentioned compounded additives can delay the aging process to the maximum extent and give the diffuser excellent weather resistance.
[0025] 3. The addition of foaming agent can improve the optical performance while reducing the material density: The introduction of foaming agent is a major innovation of the present invention. The micropores generated during the foaming process can not only effectively scatter the incident light, but also significantly reduce the density of the system. Most traditional diffusers use fillers such as titanium dioxide to improve scattering, but fillers will increase the viscosity of the system, increase the difficulty of processing, and the addition of a large amount of fillers will lead to a decrease in transmittance. The present invention cleverly uses a foaming agent to form a closed microporous structure, the pores are filled with air, and the refractive index is greatly different from that of the PC matrix, thereby enhancing the scattering ability. At the same time, the size of the micropores is much smaller than the wavelength of visible light, so scattering will not cause a significant decrease in transmittance. In addition, the internal three-dimensional interconnected microporous structure also gives the material a unique lightweight characteristic, which significantly improves the scattering performance while reducing the density, which can be said to kill two birds with one stone.
[0026] 4. The introduction of quantum dots broadens the spectrum control range and achieves high color gamut display: Introducing CdSe / ZnS core-shell structure quantum dots into the GPPS matrix is the key to achieving high color gamut display. The color purity of quantum dots is high and the half-height width is narrow. The emission wavelength can be adjusted according to the particle size to cover the entire visible light range. This fine control feature is not available in traditional phosphors. Converting part of the light excited by the blue light chip into green and red light with higher purity can effectively broaden the spectrum and greatly improve the color gamut coverage of the backlight source.
[0027] The coating layer of quantum dots and the GPPS matrix are both organic and have good compatibility, so the quantum dots can be evenly dispersed in GPPS with high dispersion stability. At the same time, the ZnS inorganic shell layer can isolate the surface defect states of quantum dots, prevent luminescence quenching, and improve quantum yield. The performance advantages of CdSe / ZnS quantum dots and the processing advantages of the GPPS matrix are perfectly combined to obtain a quantum dot diffusion plate with excellent optical properties and processing performance.
[0028] In summary, the quantum dot diffusion plate of the present invention is ingenious in its component design, and several major innovations are closely linked and complement each other: in the upper and lower surface layers, the compounding of the PC / SMA / silicone ternary system and a variety of additives jointly ensures the mechanical properties and aging resistance of the diffusion plate; the addition of a foaming agent to form micropores not only greatly improves the light scattering ability, but also gives the material lightweight characteristics; in the middle layer, the clever compounding of CdSe / ZnS quantum dots and GPPS matrix broadens the spectral regulation range and realizes high color gamut display. It can be said that the present invention gives full play to the structural characteristics and performance advantages of each component, realizes the integration of multiple performances through the sophisticated design at the molecular level, and better solves many technical problems existing in the existing quantum dot diffusion plates. The technical solution is reasonable and innovative, and has extremely high industrial application value and promotion prospects. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] The specific information of each component used in the present invention is as follows:
[0031] 1) Polycarbonate (PC): 70-99.5 parts, preferably 80-99 parts; it is polycondensed from hydroquinone and diphenyl carbonate, has a weight average molecular weight of 10,000-200,000, a melting temperature of 200-300°C, a glass transition temperature of higher than 145°C, and a melt flow rate of 5-50 g / 10 min at 300°C and a load of 1.2 kg;
[0032] 2) Styrene-maleic anhydride copolymer (SMA): 1-10 parts, preferably 1-8 parts; prepared by free radical copolymerization of styrene (C8H8) and maleic anhydride (C4H2O3), with a styrene content of 60-95 mol%, a maleic anhydride content of 5-40 mol%, a weight average molecular weight of 50000-300000, a glass transition temperature of 100-170°C, and an acid value of 10-200 mg KOH / g;
[0033] 3) Methyl (phenyl) polysiloxane (organic silicone resin): 1-10 parts, preferably 2-5 parts, which is prepared by mixed hydrolysis and condensation of dimethyldichlorosilane and diphenyldichlorosilane, with a molar ratio of methyl to phenyl of 0.5-2, a number average degree of polymerization of 10-100, and a weight average molecular weight of 500-10000;
[0034] 4) 2,2'-methylenebis(4,6-di-tert-butylphenol) (antioxidant): 0.1-1 part, preferably 0.3-0.8 part
[0035] 5) 2-hydroxy-4-hexyloxybenzophenone (ultraviolet absorber): 0.2-1 part, preferably 0.3-0.6 part;
[0036] 6) β-[3-(2H-benzotriazole-2-yl)-4-hydroxy-5-tert-butylphenyl]propionate (light stabilizer): 0.2-1 part, preferably 0.3-0.6 part;
[0037] 7) Polydimethylsiloxane (mineral oil): 0.01-0.05 parts, preferably 0.01-0.03 parts, kinematic viscosity (25°C) 10-1000mm 2 / s, refractive index (25°C) is 1.400-1.410;
[0038] 8) Benzophenone (brightening agent): 0.01-0.05 parts, preferably 0.01-0.03 parts
[0039] 9) Azodicarbonamide (foaming agent): 0.2-1 part, preferably 0.3-0.6 part, relative density is 1550-1650 kg / m 3 , the decomposition temperature is 190-240℃.
[0040] Intermediate layer materials: (1) Polystyrene (GPPS): 80-98.5 parts, preferably 85-95 parts, obtained by polymerization of styrene free radicals, with a weight average molecular weight of 100,000-500,000, and a glass transition temperature of 90-105°C; (2) CdSe / ZnS core-shell structure quantum dots: 0.5-10 parts, preferably 3-8 parts, with a core size of 2-10nm, an emission wavelength of 500-700nm, a quantum yield of ≥90%, a half-peak width of ≤30nm, oleylamine / oleic acid surface modification, and a dispersion phase stability in an organic solvent (such as n-hexane) of ≥6 months. (3) The types and proportions of antioxidants, ultraviolet absorbers, light stabilizers, mineral oils, and brighteners in the intermediate layer are the same as those in the upper surface layer.
[0041] Embodiment 1: A high temperature resistant and aging resistant quantum dot diffusion plate, the diffusion plate is composed of a PC resin matrix, quantum dots, and additives, including an upper layer, an intermediate layer, and a lower layer, wherein the upper and lower surface layer materials: 98.5 parts of PC, 1 part of SMA, 1 part of methyl (phenyl) polysiloxane, 0.2 parts of azodicarbonamide, 0.5 parts of 2,2'-methylenebis (4,6-di-tert-butylphenol), 0.4 parts of 2-hydroxy-4-hexyloxybenzophenone, 0.5 parts of β-[3-(2H-benzotriazole-2-yl)-4-hydroxy-5-tert-butylphenyl] propionate, 0.015 parts of polydimethylsiloxane, and 0.015 parts of benzophenone. The intermediate layer material: 96.5 parts of GPPS, 3 parts of CdSe / ZnS quantum dots, and the remaining additives are the same as the upper and lower layers. Preparation method: After the upper and lower surface layer materials are mixed, they are injection molded at 230°C and 25MPa, with a foaming ratio of 1.5 times; after the middle layer materials are mixed, they are injection molded at 230°C and 25MPa; the upper and lower surface layers and the middle layer are pressed together at 200°C and 20MPa.
[0042] Example 2: Upper and lower surface layer materials: PC 93 parts, SMA 5 parts, methyl (phenyl) polysiloxane 3 parts, azodicarbonamide 0.5 parts, and the amounts of other additives are the same as in Example 1. Intermediate layer materials: GPPS 93 parts, CdSe / ZnS quantum dots 5 parts, and the other additives are the same as in the upper and lower layers. Preparation method: Same as in Example 1, with a foaming ratio of 2 times.
[0043] Example 3: Upper and lower surface layer materials: PC 88 parts, SMA 8 parts, methyl (phenyl) polysiloxane 5 parts, azodicarbonamide 1 part, and the amounts of other additives are the same as in Example 1. Intermediate layer materials: GPPS 90 parts, CdSe / ZnS quantum dots 8 parts, and the other additives are the same as in the upper and lower layers. Preparation method: Same as in Example 1, with a foaming ratio of 3 times.
[0044] Example 4: Upper and lower surface material formula (weight parts): PC / SMA / organic silicon / foaming agent = 98 / 1 / 1 / 0.5, foaming ratio 2 times; middle layer material formula: GPPS / quantum dots = 93 / 5, other components are the same as above. Preparation method: the same as Example 1.
[0045] Example 5: Upper and lower surface material formula (weight parts): PC / SMA / organic silicon / foaming agent = 91 / 5 / 3 / 0.2, foaming ratio 1.5 times; middle layer material formula: GPPS / quantum dots = 90 / 8, other components are the same as above. Preparation method: the same as Example 1.
[0046] Example 6: Upper and lower surface material formula (weight parts): PC / SMA / organic silicon / foaming agent = 86 / 8 / 5 / 1, foaming ratio 3 times; middle layer material formula: GPPS / quantum dots = 96.5 / 3, other components are the same as above. Preparation method: the same as Example 1.
[0047] Comparative Example 1: Upper and lower surface material formula (weight parts): PC / organic silicon / foaming agent = 98.5 / 1 / 0.5, foaming ratio 2 times; middle layer material formula: GPPS / quantum dots = 93 / 5, other components are the same as above. Preparation method: the same as Example 1.
[0048] Comparative Example 2: Upper and lower surface material formula (weight parts): PC / organic silicon / foaming agent = 96 / 3 / 1, foaming ratio 3 times; middle layer material formula: GPPS / quantum dots = 96.5 / 3, other components are the same as above. Preparation method: the same as Example 1.
[0049] Comparative Example 3: Upper and lower surface material formula (weight parts): PC / organic silicon / foaming agent = 93 / 5 / 0.2, foaming ratio 1.5 times; middle layer material formula: GPPS / quantum dots = 90 / 8, other components are the same as above. Preparation method: the same as Example 1.
[0050] Comparative Example 4: Upper and lower surface layer material formula (weight parts): PC / SMA / organic silicon = 98 / 1 / 1; middle layer material formula: GPPS / quantum dots = 96.5 / 3, and the remaining components are the same as above. Preparation method: After the upper and lower surface layer materials are mixed, injection molding is carried out at 230°C and 25MPa; after the middle layer materials are mixed, injection molding is carried out at 230°C and 25MPa; the upper and lower surface layers and the middle layer are pressed together at 200°C and 20MPa, and cooled and demolded.
[0051] Comparative Example 5: upper and lower surface material formula (weight parts): PC / SMA / organic silicon = 92 / 5 / 3; middle layer material formula: GPPS / quantum dots = 93 / 5, other components are the same as above. Preparation method: the same as Comparative Example 4.
[0052] Comparative Example 6: upper and lower surface material formula (weight parts): PC / SMA / organic silicon = 87 / 8 / 5; middle layer material formula: GPPS / quantum dots = 90 / 8, other components are the same as above. Preparation method: the same as Comparative Example 4.
[0053] The test methods for the main performance indicators are as follows:
[0054] (1) Heat deformation temperature: measured according to ASTM D648-18 standard, with a load of 1.82 MPa and a heating rate of 2°C / min;
[0055] (2) Impact strength: According to GB / T 1843-2008, the cantilever beam notched impact strength was measured using a cantilever beam impact tester;
[0056] (3) Flexural strength and modulus: measured by three-point bending method in accordance with GB / T 9341-2008;
[0057] (4) Haze: measured using a haze meter in accordance with ASTM D1003-13;
[0058] (5) Light transmittance: measured in accordance with ASTM D1003-13 using a light transmittance test device attached to a haze meter;
[0059] (6) Color gamut coverage: measured in accordance with GB / T 34684-2017 using a spectrophotometer.
[0060] (7) Comprehensive cost performance coefficient: The comprehensive cost performance coefficient K is introduced, K = (haze × transmittance × color gamut coverage) / (density × cost price). The larger the K value, the better the comprehensive performance. The cost price is estimated based on the raw material price and ratio, and the unit is yuan / kg.
[0061]
[0062]
[0063] Table 1
[0064] As can be seen from the above table, the comprehensive performance of Examples 1-6 is significantly better than that of Comparative Examples 1-6. Among them, Example 3 has the highest K value and is the best example. The main reasons are as follows:
[0065] (1) The ternary blending and foaming of PC / SMA / silicone make the heat deformation temperature, impact strength, flexural strength and modulus of Examples 1-6 better than those of Comparative Examples 1-3 and 4-6, reflecting the mechanical enhancement effect;
[0066] (2) When the foaming ratio is moderate, the haze and transmittance are significantly improved, while the mechanical properties are not significantly reduced. For example, the foaming ratio of Examples 2 and 4 is 2 times, the haze is >90%, and the transmittance is >85%, while the mechanical properties are comparable to those of Examples 1 and 3, and better than those of Comparative Examples 1-6;
[0067] (3) When the quantum dot dosage is 3-8 parts, the color gamut coverage is high, and the color gamut is further widened as the dosage increases, and the embodiments can reach more than 90%;
[0068] (4) Compared with comparative examples 1-6, embodiments 1-6 have lower density and cost while improving transmittance and haze and broadening color gamut, thereby significantly improving K value and achieving the best cost-performance ratio.
[0069] Combined with the data in the table, the innovation of Examples 1-6 can be analyzed from the following aspects:
[0070] 1. PC / SMA blending, toughening mechanism: The introduction of SMA with good compatibility and moderate polarity in Examples 1-6 can effectively improve the compatibility of SMA and PC. SMA molecules contain both non-polar styrene segments and polar maleic anhydride segments, so they have a "quasi-interpenetrating network" compatibilization effect on PC. Under mechanical action, SMA molecules can form strain-induced SMA-g-PC block copolymers in situ, and the block copolymers form nano-scale dispersions in the PC matrix. At the same time, a transition layer is formed at the interface between PC and SMA, which can effectively transfer stress and prevent crack propagation, thereby achieving the purpose of toughening and strengthening. However, in Comparative Examples 1-3, no SMA was added, so the PC / SMA interpenetrating network structure could not be formed, and the mechanical properties were significantly reduced.
[0071] 2. Synergistic enhancement of organosilicon, hybridization mechanism: Methyl (phenyl) polysiloxane is further introduced as a hybridizing agent in Examples 1-6, and its molecules contain flexible silicon-oxygen bonds and rigid benzene rings, which can form a nano-scale dispersed organic-inorganic hybrid network structure in the PC matrix. The silicon-oxygen bonds can provide inorganic reinforcement, and the phenyl groups can form π-π stacking with the benzene rings of PC to form physical crosslinking points. The synergistic effect of the two can significantly improve the strength, modulus and heat resistance of the system. Although SMA is added to Comparative Examples 4-6, the mechanical properties are limited due to the lack of synergistic enhancement of organosilicon.
[0072] 3. Foaming to increase transmittance, optical regulation mechanism: Azodicarbonamide foaming agent is added to Examples 1-6 to form micron-scale closed foaming pores during the injection molding process. The foaming pores are filled with air, forming a large number of micro interfaces with the PC matrix, and the incident light undergoes multiple refractions and scattering at the interface, so the scattering intensity and haze are significantly improved. The size of the foaming pores is much smaller than the wavelength of visible light, and the scattering direction is random when the light passes through, and the overall optical isotropy. Therefore, while the haze is greatly improved, the transmittance does not decrease significantly. In addition, the introduction of hollow foaming pores also greatly reduces the density of the system, and the lightweight effect is obvious. In contrast, due to the lack of foaming, the optical properties of Comparative Examples 4-6 are obviously inferior to those of Examples 1-6. Although Comparative Examples 1-3 also use foaming, due to the lack of SMA toughening, the foaming pore structure is unstable, the pore wall is easy to break, and the optical performance improvement is limited. It can be seen that the ingenious combination of PC / SMA blending and foaming is the key to achieving high transmittance, high fog and lightweight.
[0073] 4. Quantum dot doping, color gamut expansion mechanism: The band gap of CdSe / ZnS core-shell structure quantum dots can be regulated by particle size to obtain narrow-band emission with high color purity. By introducing quantum dots of different particle sizes into the GPPS matrix, part of the light emitted by the blue light chip can be converted into green and red light, thereby broadening the backlight spectrum and improving the color gamut coverage. The quantum dot dosages of Examples 1-6 are 3%, 5%, and 8%, respectively. It can be seen that the color gamut coverage increases with the increase in the quantum dot dosage, and the color gamut of Example 3 is as high as 97%. This is mainly due to the reasonable particle size distribution of quantum dots, the continuous spectrum after conversion, and can cover the entire color gamut space. The introduction of the ZnS shell further passivates the surface defect states of the quantum dots, improves the quantum yield, and the color gamut expansion effect is more significant.
[0074] 5. System optimization, comprehensive performance improvement: Examples 2, 3 and 4 have the highest K values, reaching 5.28, 6.02 and 5.02 respectively, which are much higher than other examples and comparative examples. This is mainly due to the synergistic effect of PS / SMA / silicone multi-component composite and foaming and quantum dot doping. On the one hand, silicone and SMA synergistically enhance the PC matrix, while improving the mechanical properties of the system, giving it excellent toughness, making the foaming pore morphology and size distribution more uniform, the pore wall more tough, and the optical properties significantly improved. On the other hand, the high transparency of the PC matrix provides a good foundation for the luminescence of quantum dots, and the micropores produced by foaming also provide ideal dispersion sites for quantum dots, which is conducive to the uniform dispersion of quantum dots and better color gamut expansion. In addition, the reasonable ratio optimizes the density and cost of the system while improving performance, maximizing the K value. In contrast, due to the lack of key components, the synergistic effect of multiple components cannot be exerted, the performance improvement is not obvious, and the K value is generally low.
[0075] In summary, the present invention ingeniously compounds key components such as SMA, silicone, foaming agent and quantum dots into a PC matrix, and through multiple mechanisms such as block copolymerization, organic-inorganic hybridization, foaming and quantum dot luminescence, the system achieves an all-round improvement and balance in mechanical, optical, color gamut and other properties, while taking into account lightweight and low cost, and has significant innovation and practical value.
[0076] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A high temperature resistant and aging resistant quantum dot diffusion plate, characterized in that: The diffusion plate is composed of a PC resin matrix, quantum dots, and additives, and includes an upper layer, a middle layer, and a lower layer, wherein: The intermediate layer material components include the following raw materials in parts by weight: 100 parts of polystyrene, 0.5-10 parts of quantum dots, 0.1-1 parts of antioxidants, 0.2-1 parts of ultraviolet absorbers, 0.2-1 parts of light stabilizers, 0.01-0.05 parts of mineral oil, and 0.01-0.05 parts of brighteners; The upper layer and the lower layer material components include the following raw materials in parts by weight: 70-99.5 parts of PC resin, 1-10 parts of styrene-maleic anhydride copolymer, 1-10 parts of silicone resin, 0.1-1 parts of antioxidant, 0.2-1 parts of ultraviolet absorber, 0.2-1 parts of light stabilizer, 0.01-0.05 parts of mineral oil, 0.01-0.05 parts of brightener and 0.2-1 parts of foaming agent; The quantum dots are CdSe / ZnS core-shell structure quantum dots; The antioxidant is 2,2'-methylenebis(4,6-di-tert-butylphenol); The ultraviolet absorber is 2-hydroxy-4-hexyloxybenzophenone; The method for preparing a high temperature resistant and aging resistant quantum dot diffusion plate comprises the following steps: (1) Mixing the upper and lower surface materials: PC, styrene-maleic anhydride copolymer, silicone resin, antioxidant, ultraviolet absorber, light stabilizer, mineral oil, brightener and foaming agent according to the above proportions are mixed in a high-speed mixer at a speed of 500-2000 rpm for 5-30 min, and the mixing temperature is controlled at 20-80°C; (2) Mixing of the intermediate layer materials: GPPS, quantum dots, antioxidant, UV absorber, light stabilizer, mineral oil and brightener are mixed in a stirring tank at a speed of 30-200 rpm for 10-60 min according to the above ratio, and the mixing temperature is controlled at 50-120°C; (3) Three-layer co-extrusion: the mixture prepared in step (1) and step (2) is respectively added to different feed ports of a co-extruder, and a three-layer distribution die is used to perform co-extrusion at 185-230°C and 10-40 MPa, with an extrusion output of 250-500 kg / h; the temperature of each section of the single-screw extruder is set as follows: zone 1 185°C, zone 2 195°C, zone 3 215°C, zone 4 215°C, zone 5 230°C, zone 6 220°C, zone 7 215°C, and die head 210°C; the extrusion output rate is 320 kg / h; (4) Cooling and shaping: The co-extruded sheet is cooled by roller pressing, and the temperature gradually drops to room temperature to obtain the finished quantum dot diffusion plate.
2. The high temperature and aging resistant quantum dot diffusion plate according to claim 1, characterized in that: The light stabilizer is decyl β-[3-(2H-benzotriazole-2-yl)-4-hydroxy-5-tert-butylphenyl] propionate.
3. The high temperature and aging resistant quantum dot diffusion plate according to claim 1, characterized in that: The mineral oil is polydimethylsiloxane.
4. The high temperature and aging resistant quantum dot diffusion plate according to claim 1, characterized in that: The brightening agent is benzophenone.
5. The high temperature and aging resistant quantum dot diffusion plate according to claim 1, characterized in that: The foaming agent is azodicarbonamide.
